MANIFESTASI PRINSIP MORAL DALAM PEMBENTUKAN PENGADILAN PIDANA INTERNASIONAL - Danel Aditia Situngkir (Ensiklopedia of Journal, 2021)
The establishment of the International Criminal Court is an answer to the view of natural law regarding past events where to try the perpetrators of serious crimes against human rights an ad hoc international criminal court was formed which violates the provisions that have been considered rigid as law by positivists. In view of natural law, the provisions referred to in the Rome Statute are formed which are the basis for the establishment of an international criminal tribunal that has the authority to try perpetrators of crimes of genocide, crimes against humanity, war crimes and crimes of aggression. According to adherents of natural law theory, natural law doctrines will always color and inspire positive law, so that positive law always goes on the right track, both when laws are made, implemented and when used by judges in deciding cases in court. Natural law offers options through its higher-trusted rules. In this case the law of nature will function as an opposition to a tyrannical government (repeated often in history). The laws of nature are also dual in nature. At one end its function is to protect the rights, freedoms and independence of individuals, at the other end in a country, natural law as the embodiment of the highest value functions as a cry for a nation's integrity, in which operational forms of social solidarity, the common good, the public interest or social consensus.